Application of Reaching Law Approach to Design of Sliding Mode Voltage Controller for PV System - Bayindir, Mehmet Ilyas; Parlak, Koray Sener (Ieee, 2014)
Photovoltaics are one of the most important renewable energy sources. Since they are quite affected from environmental conditions, efficiently operation of PV system is valuable issue. In order to ensure this aim, the PV system must be precisely operated at maximum power point without ripples. In this study, sliding mode controller based on reaching law approach is proposed as a voltage controller providing fast and accurate tracking maximum power voltage reference. Simulation results reveal good control performance under different operation conditions.
3rd International Conference on Renewable Energy Research and Application (ICRERA) -- OCT 19-22, 2014 -- Milwaukee, WI
Keywords: photovoltaic systems; maximum power point; sliding mode control; reaching law approach